AKTIVITAS ANTIINFLAMASI EKSTRAK ETANOL DAUN GAHARU ( Aquilaria malaccensis Lamk ) PADA MENCIT PUTIH JANTAN ( Mus Musculus ) - Delladari Mayefis; Cindy Octavia; Sri Hainil; Rury Trisa Utami; Desy Maniarti Gusmali; Hesti Marliza; Nurliyasman, Nurliyasman (Nusantara Hasana Journal, 2025)
Inflammation is a complex response that occurs in blood vessel tissue due to external or internal stimuli. One plant that is known to have anti-inflammatory properties is agarwood leaves (Aquilaria malaccensis Lam). This study aims to evaluate the effect of ethanol extract from gaharu leaves on anti-inflammatory activity in male white mice (Mus musculus) and to determine the most effective dose. The experimental animals were divided into five groups, including a control group that received Na CMC and diclofenac sodium. Inflammation induction was carried out through injection of egg white solution, and measurements were carried out periodically for six hours. The analysis results showed that a dose of 300 mg/KgBW of agarwood leaf extract provided the most significant anti-inflammatory effect compared to lower doses. 100 mg/kgBB and 200 mg/kgBB